Tectonic evolution and accumulation characteristics of Carboniferous shale gas in Yadu-Ziyun-Luodian aulacogen, Guizhou Province, South China - Kun Yuan; Wen-hui Huang; Ting Wang; Shi-zhen Li; Xiang-can Sun; Xin-xin Fang; Jun-ping Xiao; Jun Guo (China Geology, 2023)
The Yadu-Ziyun-Luodian aulacogen (YZLA) developed into being NW-trending in the Late Paleozoic, and was considered as an important passive continental margin aulacogen in Guizhou Province, South China. This tectonic zone is considered a large intracontinental thrust-slip tectonic unit, which has undergone a long period of development. It was ultimately determined in the Yanshanian, where the typical Upper Paleozoic marine shales were deposited. In 2021, Well QSD-1 was deployed in the Liupanshui area at the northwest margin of the aulacogen, and obtained a daily shale gas flow of 11011 m3 in the Carboniferous Dawuba Formation. It thus achieved a breakthrough in the invesgation of shale gas in the Lower Carboniferous in South China, revealing relatively good gas-bearing properties and broad exploration prospects of the aulacogen. Being different from the Lower Paleozoic strata in the Sichuan Basin and the Yichang area of the Middle Yangtze, the development of the Carboniferous Dawuba Formation in the aulacogen exhibits the following characteristics: (1) The Lower Carboniferous shale is thick and widely distributed, with interbedded shale and marlstone of virous thickness; (2) The total organic carbon (TOC) content of the shale in the Dawuba Formation ranges from 1% to 5%, with an average of 2%, and the thermal maturity of organic matter (Ro) varies from 1% to 4%, with an average of 2.5%, indicating good hydrocarbon generation capacity; (3) The main shale in the aulacogen was formed during the fault subsidence stage from the Middle Devonian to the Early Permian. Although the strong compression and deformation during the late Indosinian-Himalayan played a certain role in destroying the formed shale gas reservoirs, comparative analysis suggests that the area covered by the current Triassic strata has a low degree of destruction. It therefore provides good conditions for shale gas preservation, which can be regarded as a favorable area for the next exploration.©2023 China Geology Editorial Office.